Estabelecimento inicial e produtividade da canola sobressemeada a soja e seus entraves em clima subtropical - Leonardi, Mateus (2023)
Overseeding consists of a technique where the seeds are distributed over the previous crop, before the end of its cycle, and is widely used after the cultivation of annual summer crops, allowing the germination and establishment of the crop to be exploited before harvest. Of the crop at the end of the cycle, with this there is a significant gain in time. The use of this sowing practice allows the intensification of cultivation systems, allowing an intensification of soil use by agricultural crops. The objective of this work was to verify which the best sowing density and the period after soaking the soil in which it is possible to establish the canola crop in sowing in soybean in the state of Rio Grande do Sul. The first study was carried out in the 2019 agricultural year, in the municipalities of Santa Maria, Giruá and Cerro Largo and in the 2020 agricultural year, in the municipalities of Santa Maria and Cerro Largo. A randomized block design was used, with 4 replications, at the densities of 3 kg ha-1 (recommended for the crop in the non-linear sowing method), 6 kg ha-1 , 9 kg ha-1 , with the control sown in no-tillage was also implanted following the recommendation for the crop soon after the soybean harvest in the first year and in the densities of 3 kg ha-1 , 4.5 kg ha-1 , 6 kg ha-1 , 7.5 kg ha-1 , 9 kg ha-1 and control in the second agricultural year. During the development cycle of the canola plants, the initial plant stand was determined, and from the density of 6 kg ha-1 the plant density closest to that recommended for the crop was reached. When the canola plants reached control, the harvest was carried out, the yield components were measured and the productivity was determined, being those from 4.5 to 6.0 kg ha-1 , in conditions subject to conditions of moisture in the surface layer of the soil, which may result in satisfactory grain yield. The second study was carried out in two experiments in the greenhouse of the department of phytotechnics at UFSM, where 9 treatments were tested with 3 replications (canola sowing performed at 1, 2, 3, 4, 5, 6, and 7 days after the end of soaking, 3 pots that were irrigated and after sowing a water depth of 30 mm was applied and 3 pots where no irrigation was performed), resulting in canola over sowing in soybeans can be done for up to two days after heavy rain cause soil moisture to rise to maximum field capacity